Drug Delivery Systems for the Oral Administration of Antimicrobial Peptides: Promising Tools to Treat Infectious Diseases - Deshayes, Caroline; Arafath, Md. Nasir; Apaire-Marchais, Véronique; Roger, Emilie (Frontiers in Medical Technology, 2022)
Antimicrobial peptides (AMPs) represent a great potential to face the global expansion of antimicrobial resistance associated to the development of multidrug-resistant pathogens. AMPs are usually composed of 10-50 amino-acids with a broad structural diversity and present a range of antimicrobial activities. Unfortunately, even if oral route is the most convenient, today approved therapeutic AMPs are mostly administrated by intravenous route. Thus, the development of novel drug delivery systems represents a promising opportunity to protect AMPs from chemical and enzymatic degradation through the gastrointestinal tract and to increase intestinal permeability leading to high bioavailability. In this review, classification and properties as well as mechanisms of AMPs used in infectiology are first described. Then, the different pharmaceutical forms present on the market for oral administration are presented. Finally, the formulation technologies, including micro- and nanoparticles-based drug delivery systems, used to improve oral bioavailability of AMPs, are reviewed.